The Relevance of the Use of Radiographic Planning in Order to Avoid Complications in Mandibular Implantology: A Retrospective Study. (12th May 2016) - Sammartino, Gilberto; Prados-Frutos, Juan Carlos; Riccitiello, Francesco; Felice, Pietro; Cerone, Vincenzo; Gasparro, Roberta; Wang, Hom-Lay
Abstract : The aim of this retrospective radiological study was to evaluate the variability of the mandibular anatomy in the presence and absence of teeth and to consider how it could influence implant planning. 187 mandibular CT DentaScans were selected from our department archive according to the inclusion criteria. The axial height, vertical height, angulation of the bone crest, and the bone available for ideal implant placement were measured. The analysis of the data shows that the mandible contour presents a constant degree of angulation. The variation of angulation in the absence of teeth was statistically significant only in the region between the canine and the first premolar and in that between the second premolar and the first molar. The difference between the crest height and the available distance to place the implant was greater in the region of the second molar while in the other regions the implant planning was made complex by postextraction resorption. Alveolar bone resorption after tooth loss can be considered as a risk factor for lingual cortical perforation during the insertion of an implant. To avoid potential intra/postoperative complications, 3D radiographic examination is recommended in order to study the mandibular anatomy and identify the risk areas.